Electrochemical and Computational Studies for Mild Steel Corrosion Inhibition by Benzaldehydethiosemicarbazone in Acidic Medium - Salman,Taghried A. (2019)
The inhibiting effect of benzaldehydethiosemicarbazone (BTSC) on the mild steel alloy corrosion in a 1 M sulfuric acidic solution was potentiostatically investigated at four temperatures, in the range of 298.15 to 328.15 K. Three BTSC concentrations, ranging from 100 to 300 mg/L, were tested. mild steel corrosion feasibility decreases with increasing inhibitor concentrations, and also with the rise in temperature. A protection efficiency of 96% was obtained at 300 mg/L, and 328.15 K. Potentiostatic polarization studies showed that BTSC acted as a mixed type inhibitor. The main kinetic effect of the BTSC inhibitor added to the sulfuric acid solution was to considerably enhance activation energy values, pre-exponential factor and activation entropy of the alloy corrosion. This was because BTSC shifted the corrosion reaction on the mild steel surface to reaction sites where energy was relatively higher than that on which the corrosion occurred in the inhibitor absence. The inhibitor adsorption followed the Langmuir adsorption isotherm. The activation thermodynamic functions (Ea, Kads, ?Gads., ?Hads. and ?Sads) were evaluated. The obtained activated parameters revealed that BTSC adsorption took place through chemisorption. Scanning electron microscopy (SEM) technique was used to provide insight into the formation of a protective film on the alloy surface. To provide a relationship between the BTSC's molecular structure and its corrosion inhibition capability, quantum chemical studies were achieved using density functional theory (DFT) at the B3LYP/6-311G level.